1667. Change in characteristics of community-onset ciprofloxacin-resistant E. coli isolates causing community-acquired acute pyelonephritis in South Korea. (31st December 2020) - Kim, Bongyoung; Kwon, Ki Tae; Ryu, Seong-yeol; Wie, Seong-Heon; Jo, Hyun-uk; Kim, Jieun; Park, Se Yoon; Hong, Kyung-Wook; Kim, Hye In; Kim, Hyun ah; Kim, Mi-Hee; Bae, Mi-Hyun; et al.
Abstract: Background: The aim of this study was to examine the change in characteristics of community-onset ciprofloxacin-resistant (CIP-R) E. coli isolates causing community-acquired acute pyelonephritis (CA-APN) in South Korea between 2010-2011 and 2017-2018. Methods: E. coli samples isolated from the blood or urine were collected from patients with CA-APN aged 19 years and more who were admitted to 8 Korean hospitals from September 2017 to August 2018, prospectively. One isolate was collected from each patient. Phylogenetic typing, multilocus sequence typing (MLST), and molecular characterization of β -lactamase resistance and plasmid-mediated quinolone resistance (PMQR) determinants were performed. The data were compared with those from the previous study with same design in 2010-2011. Results: A total of 346 and 300 isolates were collected during 2017-2018 and 2010-2011, respectively. Among them, 76 (22.0%) and 77 (25.7%) were CIP-R isolates. Significantly higher antimicrobial resistance against ampicillin (75.7% vs. 100%, P < 0.001) and cefotaxime (23.9% vs. 77.9%, P < 0.001) were observed for isolates in 2017-2018 compared to those in 2010-2011. The proportion of phylogenic group B2 had increased significantly (44.7% vs. 79.2%, P < 0.001). As for MLST, the proportion of ST131 (27.6% vs. 66.2%, P < 0.001) had increased while that of ST393 (18.4% vs. 3.9%, P =0.004) had decreased significantly. Higher proportion of CIP-R E. coli isolates in 2017-2018 had extended-spectrum β-lactamase (ESBL)/plasmid-mediated AmpC β-lactamase (PABL) (23.7% vs. 79.2%, P < 0.001) and PMQR determinant (11.8% vs. 40.8%, P < 0.001) compared to those in 2010-2011. Phlogenetic tree Analyzed by SplitsTree Conclusion: Among uropathogenic CIP-R E. coli isolates in South Korea, ST131 predominance had become more prominent and the proportion of containing ESBL/PABL and/or PMQR determinants had increased. Disclosures: All Authors : No reported disclosures